The Criminal Acts by Armed Criminal Group in Papua, â€œTreasonâ€ or â€œTerrorismâ€? - Yeksi Anakotta, Marthsian (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The designation of armed criminal groups (KKB) in Papua as a terrorist group/organization raises pros and cons because the KKB has so far been identified with the West Papua National Liberation Army (TPNPB-OPM), which is one of the armed separatist movements in Papua. The determination is motivated by violence and or armed violence carried out by the KKB which has political, ideological, and security motives, where these three motives are elements in criminal acts of terrorism. Meanwhile, according to the author, the policy carried out by the Government of Indonesia is a re-criminalization. By using the normative juridical method, the authors conclude that the determination of the KKB as a terrorist group/organization is the right policy of the Indonesian government. Based on the three motives above, the KKB can be categorized as an ethno/nationalist separatist terrorism.